2017
DOI: 10.1080/07420528.2017.1293086
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death circadian rhythm in Chagasic patients compared to non-Chagasic patients

Abstract: Circadian rhythm of SD in patient with Ch differs from those with non-Ch. In Ch patients, SD occurs predominantly during the night compared with non-Ch SD that occurs predominantly during the day especially during the morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The average sample size for studies included in this analysis was ~12,000 (ranging from n = 94 to n = 258,197). Although three other research teams (Aronow et al, 1994; Maron et al, 1994; Marques et al, 2017) identified a time-of-day rhythm in SCA incidence with similarly small sample sizes, a small sample size could have contributed to the lack of sensitivity in the findings of Watanabe et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…The average sample size for studies included in this analysis was ~12,000 (ranging from n = 94 to n = 258,197). Although three other research teams (Aronow et al, 1994; Maron et al, 1994; Marques et al, 2017) identified a time-of-day rhythm in SCA incidence with similarly small sample sizes, a small sample size could have contributed to the lack of sensitivity in the findings of Watanabe et al (2014).…”
Section: Resultsmentioning
confidence: 99%